2017
DOI: 10.1073/pnas.1616413114
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of glutamate transporter elevator mechanism by high-speed AFM

Abstract: Glutamate transporters are essential for recovery of the neurotransmitter glutamate from the synaptic cleft. Crystal structures in the outward-and inward-facing conformations of a glutamate transporter homolog from archaebacterium Pyrococcus horikoshii, sodium/aspartate symporter Glt Ph , suggested the molecular basis of the transporter cycle. However, dynamic studies of the transport mechanism have been sparse and indirect. Here we present highspeed atomic force microscopy (HS-AFM) observations of membranerec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 29 publications
12
107
0
Order By: Relevance
“…Interestingly, the populations of the OFS and the IFS in the HP2 mutants remained similar in the absence and presence of L-Asp and Na + ions ( Supplementary Table 5). This finding suggests that their OFS and IFS have similar affinities for the substrate as is also the case for the WT transporter 91 SmFRET recordings under equilibrium conditions in the presence of saturating Na + ions and L-Asp showed that the majority of GltPh molecules resided in the OFS, consistent with earlier studies 37,38,41,42,45,47 . Long OFS dwells were interspersed by brief excursions into the IFS, but long IFS dwells were also observed in some molecules and sustained dynamics were seen in others.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the populations of the OFS and the IFS in the HP2 mutants remained similar in the absence and presence of L-Asp and Na + ions ( Supplementary Table 5). This finding suggests that their OFS and IFS have similar affinities for the substrate as is also the case for the WT transporter 91 SmFRET recordings under equilibrium conditions in the presence of saturating Na + ions and L-Asp showed that the majority of GltPh molecules resided in the OFS, consistent with earlier studies 37,38,41,42,45,47 . Long OFS dwells were interspersed by brief excursions into the IFS, but long IFS dwells were also observed in some molecules and sustained dynamics were seen in others.…”
Section: Discussionsupporting
confidence: 88%
“…GltPh is a homotrimer, with each protomer consisting of a trimerization scaffold domain and a transport domain, containing the L-Asp-and Na + -binding sites. The solutes are delivered across the bilayer upon a ~15 Å "elevator" movement of the transport domain along the membrane normal from an outward-facing state (OFS) to an inward-facing state (IFS) (Figure 1A) [37][38][39][40][41][42][43][44][45][46][47] . During this transition, the transport domain forms two alternative interfaces with the scaffold involving pseudo-symmetric helical hairpins 1 and 2 (HP1 and 2) 46,48,49 .…”
mentioning
confidence: 99%
“…The tryptophan insertion does not impair glutamate uptake in Glt Ph (Appendix Fig S6A). TBOA traps Glt Ph in the OFC with open HP2 (Boudker et al , ; Ruan et al , ) and reduces fluorescence quenching (Appendix Fig S6C). Glt Ph translocation in the apo state increases quenching in choline‐based solutions (Ryan et al , ), and application of KCl leads to an additional increase in quenching efficiency (Appendix Fig S6C).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, apo state re-translocation is possible in Glt X , permitting K + -independent transport (Ryan et al, 2009). K + -coupled re-translocation is the rate-limiting step in EAATs (Grewer et al, 2000; in K + -independent Glt X , substratebound translocation is much slower (Akyuz et al, 2013;Ruan et al, 2017). This difference suggests that glutamate-bound translocation has undergone extensive evolutionary optimization in order to increase transport rates and that only K + -dependent re-translocation permitted further improvement of transport activity.…”
Section: Introductionmentioning
confidence: 99%
“…From this observation, it was revealed that this inter-trimer bR-bR contact engenders both positive and (Ruan et al 2017) Height change in MloK1 cyclic nucleotide-modulated channels (Kowal et al 2014;Rangl et al 2016) Spiral spring formation by ESCRT protein (Chiaruttini et al 2015) Stiffness map of membrane protein moieties estimated from thermal motion (Preiner et al 2015) Diffusion and interaction of outer membrane protein F (OmpF) (Casuso et al 2012) Bacteriorhodopsin responding to light Yamashita et al 2013) ATP-induced height change of Ca 2+ pump (Yokokawa and Takeyasu Moving net-like structure formed by prion covering living bacterial surface (Yamashita et al 2012;Oestreicher et al 2015) Dynamic morphological changes in living cells (Shibata et al 2015) Dynamics of nucleoporins inside nuclear porin complexes of Xenopus laevis oocytes (Sakiyama et al 2016) Responses of bacteria to antimicrobial peptide (Fantner et al 2010) a Personal communications negative cooperative effects in the decay kinetics as the initial bR recovers. Further HS-AFM studies of bR successfully revealed how bR molecules form trimers and why the trimer formation is required for the function of bR (Yamashita et al 2013).…”
Section: Hs-afm Imaging Of Biological Molecules In Actionmentioning
confidence: 91%